Air-gapped microcoxial transmission line for ultrawide band microwave and millimeter wave ICS - Tian, Yang (2014)
We present an air-gapped microcoaxial transmission line fabricated on low resistivity silicon substrate (ρ = 10 Ω·cm). The transmission line is based on a damascene copper process and has demonstrated superior microwave properties of low attenuation (<0.02 dB/mm) and a low and constant effective permittivity (∼1.02) in the frequency range of 0.1–40 GHz. The fabrication process has a low thermal budget, and can be easily integrated with the advanced Cu back-end-of-line CMOS to fabricate low-loss and high quality factor microwave and millimeter wave passives for system-on-chip applications.